Exposure to mass media chronic health campaign messages and the uptake of non-communicable disease screening in Ghana. - Irenius Konkor; Elijah Bisung; Ophelia Soliku; Martin Ayanore; Vincent Kuuire (PLoS ONE)
The main goal of this study was to examine the relationship between exposure to mass media health campaign massages and the uptake of non-communicable diseases (NCDs) screening services in Ghana and whether this relationship differs by place of residence. Available evidence suggests a general low uptake of NCDs screening in developing country settings. Unfortunately, many NCDs evolve very slowly and are consequently difficult to detect early especially in situations where people do not screen regularly and in settings where awareness is low. In this study, we contribute to understanding the potential role of the media in scaling up NCDs screening in developing countries. We fitted multivariate logistic regression models to a sample of 1337 individual surveys which were collected at the neighborhood level in three Ghanaian cities. Overall, the results show that exposure to mass media chronic NCD health campaign messages was significantly associated with increased likelihood of screening for NCDs. The results further highlight neighborhood-level disparities in the uptake of NCDs screening services as residents of low-income and deprived neighborhoods were significantly less likely to report being screened for NCDs. Other factors including social capital, knowledge about the causes of NCDs and self-rated health predicted the likelihood of chronic NCDs screening. The results demonstrate mass media can be an important tool for scaling up NCDs screening services in Ghana and similar contexts where awareness might be low. However, place-based disparities need to be addressed.